zIncubascope: Long-term quantitative imaging of multi-cellular assemblies inside an incubator. - Anirban Jana; Naveen Mekhileri; Adeline Boyreau; Aymerick Bazin; Nadège Pujol; Kevin Alessandri; Gaëlle Recher; Pierre Nassoy; Amaury Badon (PLoS ONE)
Recent advances in bioengineering have made it possible to develop increasingly complex biological systems to recapitulate organ functions as closely as possible in vitro. Monitoring the assembly and growth of multi-cellular aggregates, micro-tissues or organoids and extracting quantitative information is a crucial but challenging task required to decipher the underlying morphogenetic mechanisms. We present here an imaging platform designed to be accommodated inside an incubator which provides high-throughput monitoring of cell assemblies over days and weeks. We exemplify the capabilities of our system by investigating human induced pluripotent stem cells (hiPSCs) enclosed in spherical capsules, hiPSCs in tubular capsules and yeast cells in spherical capsules. Combined with a customized pipeline of image analysis, our solution provides insight into the impact of confinement on the morphogenesis of these self-organized systems.